Supported microwires for electroanalysis: sensitive amperometric detection of reduced glutathione - Ngamchuea, K; Lin, C; Batchelor-McAuley, C; Compton, R (American Chemical Society, 2017)
A carbon microfiber (7 μm diameter) is employed herein as an electroanalytical sensor. The fabricated sensor is cheap, disposable and requires only 150 μL of samples. The carbon fiber is surface-mounted onto an inert surface to overcome the problems of the fragility of the microwire and the possible interference of convective force due to the non-rigid nature of the wires, as well as to improve the reproducibility in length and the amperometric responses. As the cylindrical electrode is supported on a surface, the diffusion of redox-active species to the electrode is partially blocked by the substrate. A theoretical model is developed to account for this hindered diffusion. The mass-transport regime is altered from ‘linear’ at very short time, where the amperometric responses of the supported microwire closely resemble that of an isolated free standing cylinder (current ∝ electrode area), to ‘convergent’ at long time where its response now tends towards that of a hemi-cylinder of equal radius. The model is validated using chronoamperometry and cyclic voltammetry of an ideal outer-sphere redox probe, reversible ferrocene methanol oxidation. The fabricated microwire electrode is further applied to the system of irreversible 2-nitro-5-thiobenzoate oxidation used in the detection of reduced glutathione (GSH). The microwire electrode shows significantly higher ratio of Faradaic to non-Faradaic currents as compared to microdisk, macrodisk or carbon nanotube modified electrodes. Using the fabricated microwire, GSH can be detected with the sensitivity of 0.7 nA μM-1 and the limit of detection of 0.5 μM (3sB/m).